Books Received - Refuge Editor (Refuge: Canada’s Journal on Refugees, 1983)
The Refugee Documentation Project has recently acquired the following books: Transnational Legal Problems of Refugees, The Michigan Yearbook of International Legal Studies. 1981. Clark Boardman Company Ltd.